Worriers of the Pandemic: How People with Mental Disorders Cope with COVID-19 Restrictions - Zinchuk, Mikhail; Pashnin, Evgenii; Kustov, Georgii; Popova, Sofya; Voinova, Nadezhda; Gersamia, Anna; Yakovlev, Alexander; Guekht, Alla (Current Psychiatry Research and Reviews, 2024)
Objective: The aim of the study was to investigate the level of anxiety as well as the attitude toward disease and mitigation strategies in people with non-psychotic mental disorders and healthy controls. Methods: A case-control study (1:4) was conducted during a self-isolation regimen in Moscow. Cases were adult patients with NPMD admitted to the Moscow Research and Clinical Center for Neuropsychiatry. Sex and age-matched controls (individuals who have never sought psychiatric help) were selected from a cohort of 7498 Moscow residents who participated in a large cross-sectional survey delivered via social networks and popular Russian web platforms. Fisher's exact test, Mann-Whitney U test, and General linear modelling were used as statistic methods. Results: In the univariate analysis, patients with NPMD had a lower level of education and were less likely to be married. The level of the trait but not state anxiety was higher in people with NPMD. People with mental disorders were significantly more often concerned about the negative impact of the COVID-19 pandemic on their lives, were more likely to be confident that they would contract the coronavirus and their disease would be severe, showed suboptimal adherence to mitigation strategies, were dissatisfied with the amount of information they received about the COVID-19 disease, and were more concerned about becoming a victim of domestic violence. Marital status, education, use of information resources, dissatisfaction with information about COVID-19, use of public transport, paying attention to the need of others and domestic violence assessment remained significant in the general linear model. All the factors included in the multivariate model accounted for 36.4% of the variance. Conclusion: People with NPMD have a higher level of trait anxiety and are prompted to develop a constellation of maladaptive beliefs toward a pandemic. These beliefs, along with the lack of reliable information on coronavirus infection, can lead to misunderstanding and disregard of sanitary and self-isolation recommendations. Educational programs and vaccination campaigns should be sensitive to these features of people with NPMD.
Keywords: case-control study